Systematic Literature Review on Corporate Information Technology Governance in Indonesia using Cobit 2019 - Muhammad Ikhsan; Aris Puji Widodo; Kusworo Adi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
The development of Information Technology as a data communication medium is growing very rapidly. The role of information technology is of course very crucial. However, the problem that often occurs in companies or agencies is the incompatibility of technology expectations with technology that already exists in a company. Therefore, it is necessary to manage the use of information technology. This study is a literature review that aims to analyze the IT governance of companies or agencies in Indonesia that use Cobit 2019. This study uses the Systematic Literature Review (SLR) method, to answer Research Questions (RQ): RQ1 related to the company or agency that is the case study when evaluating governance using Cobit 2019, RQ2 related to the type of journal publication and year of publication of the article, and RQ3 related to recommendations from recommended domains from journal case studies. The results of the study obtained as many as 18 journal articles and proceedings were selected in the search process according to the established criteria. The results of a specific study in the context of the main question of this study, namely the governance system of 18 companies or agencies have used Cobit 2019 (answer from RQ1). The selected relevant article types include 18 articles sourced from 7 journal articles and 11 proceedings articles with a range of publication years from 2019 to 2021 (answer from RQ2). From the selected articles, it was identified that the use of the Deliver, Service, and Support (DSS) domain was the most dominant in the implementation of Cobit 2019 in companies or agencies in Indonesia. The results of the study are further described in this article.